Structure Elucidation of Complex Endotaxially Intergrown Lanthanum Barium Oxonitridosilicate Oxides by Combination of Microfocused Synchrotron Radiation and Transmission Electron Microscopy. Issue 50 (3rd August 2021) - Gamperl, Lisa; Neudert, Lukas; Schultz, Peter; Durach, Dajana; Schnick, Wolfgang; Oeckler, Oliver
Abstract: Single‐crystalline domains in intergrown microcrystalline material of the new compounds Ba22.5+ x La55− x [Si129 N240− x O x ]O3 :Ce 3+ and Ba25.5+ x La77− x [Si170 N312− x O9+ x ]O4 :Ce 3+ were identified by transmission electron microscopy (TEM). Precise diffraction data from these domains were collected with microfocused synchrotron radiation so that crystal structure elucidation of the complex disordered networks became possible. They are composed of two different interconnected slabs of which one is similar in both compounds, which explains their notorious intergrowth. The distribution of Ba and La is indicated by the analysis of bond‐valence sums and by comparison with isostructural Sr28.5+ x La75− x [Si170 N312− x O9+ x ]O4 . Ce 3+ doping leads to yellow luminescence. This is a showcase that highlights the discovery and accurate characterization of new compounds relevant for luminescence applications from heterogeneous microcrystalline samples by exploiting the capability of the combination of TEM and diffraction using the latest focusing techniques for synchrotron radiation. Abstract : Single‐crystalline domains of microcrystalline intergrown oxonitridosilicate oxides Ba22.5+ x La55− x [Si129 N240− x O x ]O3 and Ba25.5+ x La77− x [Si170 N312− x O9+ x ]O4 and related Sr analogues were identified by TEM. Diffraction data collected with microfocused synchrotron radiation reveal extraordinarily complex tetrahedra networks. This combination of analytical methods enables the characterization of new luminescent materials in heterogeneous powder samples.